Parasitism and food web structure in defoliating Lepidoptera – Parasitoid Communities on Soybean - Avalos, D. S. (2016)
Food webs are usually regarded as snapshots of community feeding interactions. Here, we describe the yearly and cumulative structure of parasitoid–caterpillar food webs on soybean in central Argentina, analyzing parasitism rates and their variability in relation to parasitoid diversity and food web vulnerability in the system. Lepidoptera larvae were collected along four seasons from soybean crops and reared in laboratory to obtain and identify adults and parasitoids. Eleven species of defoliating Lepidoptera and ten parasitoid species were recorded. Food web statistics showed rather low annual variability, with most variation coefficients in the order of 0.20 and generality showing the most stable values. Parasitism showed the highest variability, which was independent of parasitoid diversity and food web vulnerability, although parasitism rates were negatively related to parasitoid richness. Our study highlights the need to consider food web structure and variability in order to understand the functioning of ecological communities in general and in extensive agricultural ecosystems in particular.